3D printing of porous poly(ε-caprolactone)-poly(trimethylene carbonate)-poly(ε-caprolactone) triblock copolymers and nano-apatite composite structures - Aysun Güney; Lena Kernebeck; Dirk W. Grijpma (eXPRESS Polymer Letters)
Biodegradable porous poly(ε-caprolactone)-poly(trimethylene carbonate)-poly(ε-caprolactone) triblock copolymers (PCL-b-PTMC-b-PCL) were synthesized by sequentεial polymerization of trimethylene carbonate (TMC) and ε-caprolactone (CL), and novel composites of PCL-b-PTMC-b-PCL with different amounts of nano-apatite (nAp) were prepared. This PTMC-based polymer matrix, which does not degrade into acidic compounds, together with the nanometer-sized apatite, which influences cell behavior, is an ideal bone regenerative material. Solvent casting these composites from chloroform solutions yielded solid films with excellent handling properties. The E-modulus of the nano-composite materials increases with nAp content, while toughness, tensile strength and elongation at break decrease. Using EC as solvent, porous composite films of PCL-b-PTMC-b-PCL and nAp could readily be prepared. The composites in EC were processed into form-stable designed tissue engineering scaffolds by 3D printing at relatively mild conditions. Besides the pore network structure with pores of 530 to 620 μm which corresponded to the design, smaller pores of 5–30 μm (due to EC crystallization) and even smaller ones of 200–500 nm (resulting from liquid-liquid exchange upon extraction of the solvent in the polymer rich phase) were observed in the printed composite scaffolds.